2020
DOI: 10.1021/acsami.0c03822
|View full text |Cite
|
Sign up to set email alerts
|

Tanshinone IIA Delivery Silk Fibroin Scaffolds Significantly Enhance Articular Cartilage Defect Repairing via Promoting Cartilage Regeneration

Abstract: Cartilage tissue engineering is a promising approach for repairing articular cartilage defects and requires proper scaffolds and necessary growth factors. Herein, tanshinone IIA (TAN) delivery silk fibroin scaffolds were prepared for efficient cartilage defect repair by bioactivities of TAN. By incubating with the TAN delivery silk fibroin scaffold, the transcription of the chondrocytic activity-related genes was enhanced in chondrocytes, and it also can inhibit cell apoptosis and reduce the oxidative stress b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
45
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 42 publications
(45 citation statements)
references
References 55 publications
0
45
0
Order By: Relevance
“…All animal experiments in this study were approved by the Animal Care and Ethics Committee of Hunan Academy of Chinese Medicine. Rabbit articular chondrocytes were isolated and cultured according to our previous publication [ 33 ]. In brief, articular cartilage was isolated from the knee joints of New Zealand white rabbits (1 week old) and cut into small pieces (<1 mm 3 ).…”
Section: Methodsmentioning
confidence: 99%
“…All animal experiments in this study were approved by the Animal Care and Ethics Committee of Hunan Academy of Chinese Medicine. Rabbit articular chondrocytes were isolated and cultured according to our previous publication [ 33 ]. In brief, articular cartilage was isolated from the knee joints of New Zealand white rabbits (1 week old) and cut into small pieces (<1 mm 3 ).…”
Section: Methodsmentioning
confidence: 99%
“…Human articular cartilage ECM + AD-MSCs/chondrocytes [27] HA/collagen/fibrinogen + SMSCs + rhTG-4 [28] Human placenta + BM-MSCs ± PRP [30] Alginate spheres + chondrocytes/chondrons [36] 02 Scaffold-Free Strategies Human freeze-dried cancellous bone + human chondrocyte sheets [43] Human chondrocytes ± human synoviocytes [44] hAMSCs cell sheets + cartilage particles [46] 03 Injectables AD-MSCs ± HA [49] Open-porous PLGA microspheres + BM-MSCs [50] MSCs + chondrocytes [51] PEG/ApoPep-1/TCO + chondrocytes [52] E7-Exo + SF-MSCs + KGN [53] 04…”
Section: Scaffold-based Strategiesmentioning
confidence: 99%
“…In their work, Chen et al (2020) coupled SF scaffolds with TAN and seeded them with New Zealand white rabbit chondrocytes. Assessments of the novel scaffold in vitro and in vivo using nude mice (subcutaneous implantation) and New Zealand white rabbit models with full-thickness cartilage defects revealed that chondrocytes in these scaffolds can produce hyaline-like cartilage and thus promote cartilage regeneration better than SF scaffolds alone, mainly when the concentration of TAN is 10 μg/mL [ 36 ].…”
Section: Tissue Engineering Strategies For Articular Cartilage Regenerationmentioning
confidence: 99%
“…Importantly, STS prevented articular cartilage degradation by inhibiting apoptosis and in ammatory cytokine expression levels, suggesting that it might be used to treat osteoarthritis (OA) [9][10][11][12]. Furthermore, STS has been shown to suppress chondrocyte dedifferentiation [13,14].…”
Section: Introductionmentioning
confidence: 99%